2023
DOI: 10.3390/vaccines11091426
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Booster Hesitancy among Hispanic Adults: A Cross-Sectional Study from the Puerto Rico Community Engagement Alliance against COVID-19 Disparities (PR-CEAL)

Hérmilis Berríos,
Andrea López-Cepero,
Cynthia M. Pérez
et al.

Abstract: Hispanic/Latino communities have suffered a disproportionate burden of the COVID-19 pandemic. Although Puerto Rico has one of the highest COVID-19 primary series vaccination rates nationwide, this estimate contrasts with the reported booster doses’ low uptake. This study aimed to assess health belief correlates of COVID-19 vaccine booster uptake. Using a convenience sampling approach, the Puerto Rico-Community Engagement Alliance (PR-CEAL) conducted a cross-sectional study where 787 participants were recruited… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The project also aimed to understand perceived barriers and enablers of vaccination, testing behaviors, and various modules related to health behaviors and their impact on mental health outcomes during the pandemic. Adopting a cross-sectional design, the study recruited 784 participants in Puerto Rico through online and in-person channels between December 2021 and January 2022 ( 9 ).…”
Section: Pr-ceal Infrastructurementioning
confidence: 99%
See 2 more Smart Citations
“…The project also aimed to understand perceived barriers and enablers of vaccination, testing behaviors, and various modules related to health behaviors and their impact on mental health outcomes during the pandemic. Adopting a cross-sectional design, the study recruited 784 participants in Puerto Rico through online and in-person channels between December 2021 and January 2022 ( 9 ).…”
Section: Pr-ceal Infrastructurementioning
confidence: 99%
“…An analysis of the HBM constructs revealed that 83% of these constructs exhibited significant associations with booster refusal. Notably, participants who disagreed with the notion that receiving the booster dose made them feel less worried about COVID-19 or believed that the vaccine decreased their chances of contracting COVID-19 demonstrated higher prevalence ratios for booster refusal ( 9 ). Participants who expressed concerns about booster side effects, efficacy, and safety were significantly more likely to refuse the booster.…”
Section: Pr-ceal Infrastructurementioning
confidence: 99%
See 1 more Smart Citation